Impacts of Nitrogen and Phosphorus: From Genomes to Natural Ecosystems and Agriculture - Guignard, Maïté S.; Leitch, Andrew R.; Acquisti, Claudia; Eizaguirre, Christophe; Elser, James J.; Hessen, Dag O.; Jeyasingh, Punidan D.; Neiman, Maurine; Richardson, Alan E.; Soltis, Pamela S.; Soltis, Douglas E.; Stevens, Carly J.; et al. (Frontiers in Ecology and Evolution, 2017)
Nitrogen (N) and/or phosphorus (P) availability can limit growth of primary producers across most of the world’s aquatic and terrestrial ecosystems. These constraints are commonly overcome in agriculture by applying fertilizers to improve yields. However, excessive anthropogenic N and P inputs impact natural environments and have far-reaching ecological and evolutionary consequences, from individual species up to entire ecosystems. The extent to which global N and P cycles have been perturbed over the past century can be seen as a global fertilization experiment with significant redistribution of nutrients across different ecosystems. Here we explore the effects of N and P availability on stoichiometry and genomic traits of organisms, which, in turn, can influence: i) plant and animal abundances; ii) trophic interactions and population dynamics; and iii) ecosystem dynamics and productivity of agricultural crops. We articulate research priorities for a deeper understanding of how bioavailable N and P move through the environment and exert their ultimate impacts on biodiversity and ecosystem services.